Does Flexible Working Time Make Start-up Company Workers More Engaged? - Silitonga, Michelle Astari Rumiris; Batubara, Megawati (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2023)
Currently, one business model that is particularly prevalent in Indonesia and has an impact on state revenue is start-up. There is one technology start-up in Indonesia that also influences economic development in Indonesia, namely company X. Behind the good performance of technology start-ups, there are roles of workers, culture, and the environment. Start-up X has a culture, namely a flexible work arrangement in which employees can have the freedom to choose when and where to work. This flexibility also has a lot of impact on the way of work and also the daily life of the workers. Flexible work arrangement (FWA) works as resources in a company. The high freedom affects workers’ engagement. Thus, the purpose of this study was to determine the effect of flexible work arrangements on the work engagement of employees at Start-up Company X. This research was conducted on 102 workers selected with a convenience sampling technique. This study uses a non-experimental research design with a correlational study method. Data collection was carried out using the Flexible Work Arrangement measuring tool adapted from Umi Farida (2020) and the Indonesian Utrecht Work Engagement Scale (UWES)-17 questionnaire from Schaufeli (2004). The results of this study indicate that there is a significant effect (p<0.001; R2=0.245) of the flexible work arrangement on the work engagement of employees at start-up company X. It means if there is a change in flexible work arrangement, it will impact the result of the work engagement. Our research adds new insights about the impact of FWA and WE variables on startup companies. Furthermore, when FWA is supported by adequate job resources and balanced with job demands, it can improve employee’s WE in startup companies. This study can provide information on future research on FWA and WE variables in start-up companies and with FWA supported by job resources that are balanced with job demand, will increase the WE of start-up company workers.